A comparative study of glial and non‐neural cell properties for transplant‐mediated repair of the injured spinal cord. Issue 4 (16th January 2013) - Toft, Andrew; Tome, Mercedes; Barnett, Susan C.; Riddell, John S.
Abstract Cell transplantation is one strategy for encouraging regeneration after spinal cord injury and a range of cell types have been investigated for their repair potential. However, variations in study design complicate determination of which cells are most effective. In this study we have carried out a direct comparison of the regenerative and integrative properties of several cell preparations following transplantation into the lesioned rat spinal cord. Transplants included: (i) purified olfactory ensheathing cells (OECs) and (ii) fibroblast‐like cells, from olfactory bulb (OBFB‐L), (iii) a 50:50 mixture of (i) and (ii) (OEC/OBFB‐L), (iv) dissociated nasal mucosa (OM), (v) purified peripheral nerve Schwann cells (SCs), (vi) peripheral nerve fibroblasts, and (vii) skin fibroblasts (SF). All transplants supported axonal regeneration: OECs and SCs promoted the greatest regeneration while OBFB‐like cells were least efficient and mixed cell populations were less effective than purified populations. Tract‐tracing experiments demonstrated that none of the cell types promoted regeneration beyond the lesion. Although all cell types prevented cavity formation, the extent of astrocytic hypertrophy [GFAP immunoreactivity (IR) at the transplant/lesion site] differed markedly. OECs and SCs were associated with the least GFAP‐IR, fibroblasts and fibroblast‐like cells resulted in greater GFAP‐IR while hypertrophy surrounding transplants of OM was most extensive. These differences in host‐transplant reactivity were confirmed by transplanting cells into normal spinal cord where the cellular interaction is not complicated by injury. Thus, purified glial cells have advantages for transplant‐mediated repair, combining maximal support for axonal regeneration with a minimal astrocytic reaction around the transplant site. © 2013 Wiley Periodicals, Inc.